Reaction mechanisms in organic chemistry - Balci, Metin (Weinheim : Wiley-VCH, 2022)
Dr. Metin Balci delivers an excellent textbook for understanding organic reaction mechanisms. It includes the most important reaction types, including substitution, elimination, addition, pericyclic, and C-C coupling reactions. Each chapter contains problems and accompanying solutions that cover central concepts in organic chemistry. Students will learn to understand the foundational nature of ideas like Lewis acids and bases, electron density, the mesomeric effect, and the inductive effect via the use of detailed examples and an expansive discussion of the concept of hybridization. Perfect for students of chemistry, biochemistry, and pharmacy, Reaction Mechanisms in Organic Chemistry will also earn a place in the libraries of researchers and lecturers in these fields seeking a one-stop resource on organic reaction mechanisms.
Includes the solutions and index
The book offers a way for undergraduate and graduate students to understand???rather than memorize???the principles of reaction mechanisms.
Keywords: Aromaticity -- Nitration -- Sulfonation